Ultrafast crystallization of ordered mesoporous metal oxides and carbon from block copolymer self-assembly and joule heating - Wang, Leyan (2022)
Conventional heat treatments to generate well-ordered and crystalline mesoporous oxide and carbon structures are limited by long durations and annealing temperatures that can cause mesostructural collapse. This paper describes a facile strategy coupling block copolymer-directed self-assembly with high-power Joule heating to form highly crystalline and well-ordered mesoporous oxide and carbon nanostructures within second timeframes. The combined approach is compatible with various functional self-assembled hybrid systems with a range of crystallization temperatures, generating mesoporous composites of γ-Al2O3-carbon, γ-Al2O3/MgO-carbon, and anatase-TiO2-carbon with p6mm symmetry, non-close-packed mesoporous carbon, as well as hierarchical mesoporous α-Fe2O3-carbon structures. Removing the polymer/carbon gives well-defined, highly crystalline mesoporous all-γ-Al2O3 and all-anatase-TiO2 structures. Impregnation of chloroplatinic acid followed by Joule heating yields platinum nanoparticles decorated on the channel walls of mesoporous γ-Al2O3-carbon structures. The resultant Joule-heating-induced well-ordered crystalline mesoporous oxide and oxide-carbon structures have high thermal and structural stabilities and exhibit better performances in CO2 adsorption capacity and lithium-ion batteries than conventional heat-treated counterparts. This approach represents an energy-efficient and time-saving route toward ordered porous materials with high surface area and pore accessibility for a wide range of environmental applications such as carbon sequestration, renewable energy storage, and environmental filtration.